Experimental and numerical studies on the heat transfer improvement of a latent heat storage unit using gradient tree-shaped fins. (January 2022) - Huang, Yongping; Cao, Dongcheng; Sun, Dongke; Liu, Xiangdong
Highlights: Latent heat storage units with uniform and gradient tree-shaped fins are studied. Gradient fins facilitate synergistic enhancement of convection and conduction. Gradient fins further reduce the melting duration by 9% than uniform layouts. Non-uniform transport path of gradient fins is not conducive to solidification. Abstract: To improve the thermal performance of horizontal latent heat storage (LHS) units, this study investigates two innovative LHS units using uniform and gradient tree-shaped fins. By coupling visualization experiments and three-dimensional numerical simulations, the melting/solidification behavior and thermal properties of innovative LHS units are comprehensively analyzed and compared with traditional LHS units. The results show that tree-shaped fins facilitate heat diffusion from point to area, breaking the heat transport hysteresis in traditional LHS units, thus accelerating the melting/solidification rate. During the melting process, the gradient tree-shaped fins strengthen the heat transfer in lower parts of the LHS unit and extend the convective heat transfer duration in upper regions, promoting the synergistic strengthening of natural convection and heat conduction in the late melting stage. Compared to the uniform fin layout, the gradient tree-shaped fins effectively increase the melting rate, shortens the melting duration by 9%, and further improve the overall temperature uniformity of LHS units. However, the non-uniform transport path of gradient tree-shaped fins is not conducive to solidification heat transfer with conduction as the primary thermal regime, which increases the temperature gradient of LHS units and prolongs the solidification duration by 57.4% compared to the uniform tree-shaped fins.